PENGEMBANGAN LKS BERBASIS CERITA MODEL RECIPROCAL TEACHING MATERI PENYAJIAN DATA KELAS VII UNTUK MENINGKATKAN PEMAHAMAN KONSEP SISWA - Kumarani Mita Pratama (Universitas Pekalongan, 2019)
Based on the results of observation, interview and questionnaire analysis of students’ needs, researchers obtained information that there were error typing in the 2013 curriculum textbook used. Moreover, students of SMP Negeri 1 Wonopringgo had a lack of conceptual understanding. Based on the results of students’ needs analysis in certain class stated that students need worksheet as a companion of textbooks material, there were 43.75% of the total students said worksheet with picture story is more interesting while 56.25% students said worksheet with stories related to daily life is more interesting to learn. The purpose of this research was to develop Story-Based Students’ Worksheet used by Reciprocal Teaching Model for Data Presentation Material Class VII that is valid and feasible to increase students’ conceptual understanding. This research is R&D (Research and Development) using Borg and Gall model. The instruments used by researchers were observation sheet, interview guide, questionnaire of student requirement and product validation questionnaire. Questionnaires student needs were used to find out the needs of students based on the questions given. While the validation sheet was used to test validity of the validated product by 8 validators consisting of 5 teachers and 3 lecturers. The results of validation were analized quantitative used by Aiken’s formula. Based on the research, validator stated students’ worksheet was feasible to be used in learning with revision. Researchers improved the students’ worksheet according to the direction of the validator, both in terms of appearance and content of students’ worksheet. Furthermore after doing the second validation, the result of 8 validators assesment analysis obtained 0,832 with extremely valid criteria. It showed that the worksheet is valid to increase students’ conceptual understanding and also suitable to be used in learning process.